ASSOCIATION BETWEEN CONNECTIVE TISSUE DISORDERS AND LUMBAR DISC HERNIATION: A SYSTEMATIC REVIEW - Maciej Błądziński; Karolina Błądzińska; Joanna Kłosowska; Anna Opalińska; Cezary Lubas; Paula Folta; Kacper Szeląg; Małgorzata Zach; Piotr Świerczek; Antoni Kujawski (International Journal of Innovative Technologies in Social Science, 2025)
Lumbar disc herniation (LDH) is one of the most common structural causes of low back pain worldwide. While mechanical overload and age-related degeneration are widely recognized as key factors, recent research suggests that connective tissue disorders (CTDs) and related genetic abnormalities may also play a significant role in disc pathology. This systematic review aimed to evaluate the current evidence on the relationship between CTDs and LDH from clinical, genetic, and mechanistic perspectives. A comprehensive literature search was performed in PubMed and Google Scholar up to April 2025, according to PRISMA guidelines. Thirteen studies were included, encompassing genome-wide association studies, cohort and case-control studies, experimental animal models, and proteomic analyses. Several genetic variants related to extracellular matrix components and sulfate transport, including CHST3, ADAMTS17, and COL11A2, were found to be associated with lumbar disc degeneration. Clinical studies showed a potential link between joint hypermobility or rheumatoid arthritis and higher LDH prevalence or postoperative complications, although findings were inconsistent. Mechanistic models highlighted local molecular changes, such as altered TGF-β signaling and overexpression of CILP or AEBP1, which may impair disc integrity. Despite growing molecular insights, the clinical correlation between CTDs and LDH remains insufficiently explored. More longitudinal studies with standardized definitions of CTDs and better genetic profiling are necessary to clarify these associations and improve patient stratification.